Pelatihan Penyusunan Modul Pembelajaran Berbasis Proyek (Project Based Learning) bagi Guru SMK PGRI 39, Jakarta - Eliyani, Citra; Widya Lestari, Ambar; Puji Rahayu , Krida (Lembaga Kajian Demokrasi dan Pemberdayaan Masyarakat (LKD-PM), 2024)
The purpose of this community service is to provide understanding and material on the importance of preparing Project-Based Learning-based learning modules, providing skills training to teachers in Vocational High Schools (SMK) in making or compiling Project-Based Learning-based modules, and providing assistance and training in teachers in Vocational High Schools (SMK) in creating or compiling modules based onProject Based Learning. This service was held at SMK PGRI 39 Jakarta. The service methods used are lectures, questions and answers, and simulations. The participants of this service activity are teachers of SMK PGRI 39 Jakarta. The results of this service can have a positive impact, including: teachers can improve their ability to prepare teaching modules by understanding each component of the preparation of teaching modules, teachers are more enthusiastic about preparing teaching modules regularly, and teachers are motivated to continue to improve their pedagogical skills. It is hoped that this service can add useful knowledge in terms of the preparation of teaching modules regularly, especially project-based teaching modules that are relevant to learning objectives at SMK.